2013
DOI: 10.1002/bmc.2946
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer in microextraction by packed sorbent for the simultaneous determination of local anesthetics: lidocaine, ropivacaine, mepivacaine and bupivacaine in plasma and urine samples

Abstract: This study presents the use of molecularly imprinted polymer (MIP) as packing material for microextraction by packed syringe (MEPS) to achieve higher extraction selectivity. Pentycaine was used as template for MIP. Development and validation of the determination of lidocaine, ropivacaine, mepivacaine and bupivacaine in human plasma and urine samples utilizing MIP-MEPS and liquid chromatography-tandem mass spectrometry (LC-MS/MS) were carried out. The MEPS MIP-cartridge could be used for 100 extractions before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 40 publications
0
32
0
1
Order By: Relevance
“…Möder and collaborators reported the use of custom-made MEPS BINs packed with MIPs for different wastewater contaminants [18,26,32], and Daryanavard et al [61] use the same approach to analyze different anesthetics in plasma and urine. In another report, carbon nanotubes have been combined with MEPS extraction followed by capillary electrophoresis to allow the analysis of trace levels of ionic liquids in river water samples [46].…”
Section: 3promising Meps Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Möder and collaborators reported the use of custom-made MEPS BINs packed with MIPs for different wastewater contaminants [18,26,32], and Daryanavard et al [61] use the same approach to analyze different anesthetics in plasma and urine. In another report, carbon nanotubes have been combined with MEPS extraction followed by capillary electrophoresis to allow the analysis of trace levels of ionic liquids in river water samples [46].…”
Section: 3promising Meps Applicationsmentioning
confidence: 96%
“…The lack of selectivity is the main problem with the use of common sorbents in MEPS. To overcome this problem, molecularly-imprinted polymers (MIPs) with highly specific recognition abilities for target molecules were found to be appropriate [26,32,61].…”
Section: Various Types Of Sorbents Used In Mepsmentioning
confidence: 99%
“…ME was calculated by comparing the peak areas of analytes between the samples [376], which were post-spiked to dry extracted blank human plasma, urine, and standard solutions at low, medium, and high QC samples concentrations (n=5). Results showed that the matrix has no effect on the quantification results in this technique (Table 4).…”
Section: Matrix Effectmentioning
confidence: 99%
“…The matrix effect (ME) for these substances ranged from 50% to 146% using protein precipitation while it was less than 20% using MIP-MEPS. This suggests that cleaner extracted samples can be obtained with MEPS and that matrix related problems can be reduced [147]. In comparison with conventional SPE, the MEPS method can handle smaller sample volumes (10–100  μ L).…”
Section: Microextraction By Packed Sorbent (Meps)mentioning
confidence: 99%